An onboard-eye-to-hand visual servo and task coordination control for aerial manipulator based on a spherical model. (April 2022) - Lai, Ningbin; Chen, Yanjie; Liang, Jiacheng; He, Bingwei; Zhong, Hang; Wang, Yaonan
Abstract: Compared with the unmanned aerial vehicle (UAV), the aerial manipulator extends the ability to interact with the environment by using the onboard manipulator. The complex dynamic characteristics of the combined system increase the challenges of accurately control the aerial manipulator to approximate the target object. In this paper, an onboard-eye-to-hand visual servo and task coordination control strategy is proposed for the aerial manipulator to enhance the accurate manipulation and flight stability. By establishing a new spherical coordinate error equation, the flying platform (quadrotor) and onboard manipulator can be controlled simultaneously. Meanwhile, the multi-task coordinated control scheme is adopted to achieve precise positioning and grasping of the target object, including estimating the object pose, dynamically compensating the change of the center of gravity of the aerial manipulator, and avoiding the onboard manipulator joint limitations. The stability of the closed-loop system is analyzed by the Lyapunov method. Finally, the feasibility of the proposed visual servo method is verified in simulations and real-world outdoor experiments, respectively. The strengths of the proposed method are demonstrated by comparing it with the conventional visual servo method.